How does a partner's acquisition affect the value of the firm's alliance with that partner? - Lavie, Dovev; Lunnan, Randi; Truong, Binh Minh T. (Strategic Management Journal, 2022)
Abstract Research Summary How does an acquisition initiated by a firm's alliance partner affect the value that the firm can create and capture from its alliance with that partner? We conjecture that the similarity between the businesses of the firm and its partner's acquisition target restricts the firm's ability to create and capture value from its alliance, whereas the complementarity between their businesses enhances the firm's gain from its alliance. We further expect relational embeddedness between the firm and its partner to mitigate the competitive tension associated with similarity while reinforcing synergies ascribed to complementarity. Our analysis of 361 firms and their 590 alliances with 91 partners that acquired 164 targets during 2000–2016 supports our predictions about business similarity and complementarity but refutes those concerning relational embeddedness. Managerial Summary When a firm's partner engages in an acquisition, this can impact the value of their alliance. We show that when the acquired target competes with the firm, the value of the alliance declines. In turn, when the target and firm's businesses are complementary, the alliance creates more value. We also find that when the firm and the partner had extensive experience working together, this reinforces the negative effect of business similarity with the target, probably because of perceived betrayal and knowledge leakage. Joint experience also reduces the value of complementarity, likely due to the difficulty of modifying collaborative practices. We encourage managers to scrutinize their partners' corporate initiatives, reduce commitment when the partner acquires a competing target, and leverage new complementarities following the partner's acquisitions.